Implementasi Fuzzy Tsukamoto Untuk Menentukan Kepala Sekolah Berprestasi Tingkat SMK - vivin ayu lestari; Baskoro Singgih Anindito; Andi Maulidinnawati Abdul Kadir Parewe (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2019)
One of the factors that influence in improving the quality of education is the quality of school principals who have good achievements. An award for selecting outstanding principals at the SMK level is an important thing to do in an effort to support the progress of educational institutions because with the selection of outstanding principals, the quality of education and school management will be further improved. This study uses the Fuzzy Tsukamoto method to help determine the ranking of outstanding principals. The input variables used were performance, portfolio, written test, publication assessment, and interviews. The result of the calculation of the Spearman correlation coefficient is 0.92, so it is a very strong correlation category.